Preoperative education in hip and knee arthroplasty patients in Bloemfontein - Roline Y. Barnes; Karen Bodenstein; Nadia Human; Jacques Raubenheimer; Jodri Dawkins; Carmen Seesink; Jonè Jacobs; Jolien van der Linde; Ruan Venter (AOSIS, 2018)
Background: Total hip arthroplasty (THA) and total knee arthroplasty (TKA) are frequently performed surgeries worldwide. Preoperative education enhances patient physiotherapy management and satisfaction and should be tailored to patients' educational needs. Limited research is available regarding the preoperative educational needs for these patients. Objectives: To determine the extent of preoperative education received and the preoperative educational needs of patients undergoing THA and TKA. Method: A structured interview utilising a self-developed questionnaire was used and included questions exploring preoperative education, educational needs, method of education and health care professional providing education. A total of 14 THA and 36 TKA patients, 2-4 days post-operatively at private hospitals in Bloemfontein, were conveniently sampled. Results: All participants had arthroplasties because of osteoarthritis. All participants with THA and 35 (98%) participants with TKA received preoperative education from orthopaedic surgeons, and 8 (57%) participants with THA and 9 (25%) participants with TKA received preoperative education from physiotherapists. Education was mostly given as pamphlets months before the surgery. Participants received the least amount of information regarding exercises, especially preoperative exercise, pain relief and activities of daily living. Conclusion: This study highlights the need for improvement in patient engagement and education, together with enhanced health care practitioner communication and collaboration. Patient centeredness and individualised THA and TKA preoperative education programmes are recognised as a necessary attribute of quality health care and can lead to improved THA and TKA outcomes. The importance of exercise as part of preoperative interprofessional education in the management of THA and TKA should be emphasised as exercise is the cornerstone for rehabilitation of THA and TKA. Clinical implications: This study aimed to emphasise the importance of tailored preoperative education for THA and TKA patients to improve patient outcomes.